Efficacy of single injection of FSH dissolved in polyvinylpyrrolidone on superovulatory response in crossbred cows - Karunakaraw, M; Veerapandian, C (The Indian Journal of Animal Sciences, 2011)
This study was undertaken to investigate the utility of polyvinylpyrrolidone as a vehicle to combine whole dose of FSH as single injection to induce superovulation in crossbred cows. Crossbred cows (9 in each group) were superovulated with (i) 18 mg of FSH in 8 divided, descending intra-muscular doses for 4 days, and (ii) with a single intra-muscular injection of 18 mg FSH in 10 ml of 30% polyvinylpyrrolidone. Luteolytic doses of prostaglandin F2u 25 and 15 mg were injected at 48 and 60 h later respectively. The cows detected at estrus were inseminated twice at 12 h interval. Superovulatory response was assessed by rectal palpation on day 7 post breeding and cows with> 2 CL were flushed using DPBS. Blood samples were collected on the days of initiation of gonadotropin treatment, prostaglandin F2o. injection, superovulated estrus and embryo collection, and the plasma was analysed for progesterone level by standard RIA technique. The mean number ofovulations and total number ofembryos/oyum recovered were significantly higher in multiple injection group than the single injection group. The mean progesterone concentration on the day of embryo collection in multiple injection group was significantly higher than the other group. The present study demonstrated that a single intra muscular injection of 18 mg FSH dissolved in polyvinylpyrrolidone was not capable of inducing sufficient superovulatory response to that of multiple FSH injections in crossbred cows.